Effectiveness of Yushen Hezhi therapy for postmenopausal osteoporosis: An overview of systematic reviews of randomized controlled trials - Zhao, Jinlong; Xiao, Xiao; Zhou, Guanghui; Xu, Nanjun; Liu, Jun (Frontiers in Endocrinology, 2022)
Objective To review systematic reviews (SRs) and meta-analyses (MAs) of Yushen Hezhi therapy (YSHZT) for postmenopausal osteoporosis (PMOP) to provide an evidence-based recommendation for researchers and decision makers. Methods We searched the PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), China Biology Medicine (CBM) and Wanfang databases for published SRs and MAs on YSHZT for the treatment of PMOP. The retrieval time was limited to July 2022. The Assessing the Methodological Quality of Systematic Reviews (AMSTAR)-2 tool and Grades of Recommendations, Assessment, Development, and Evaluation (GRADE) classification system were used to evaluate the methodological quality and the evidence quality of the SRs and MAs, respectively. Results A total of 14 SRs and MAs involving 14720 cases of PMOP were included. The results of the methodological quality evaluation indicated that there were no studies with medium- or high-quality methodology included in the study and that there were 9 and 5 low- and very low-quality studies, respectively. The GRADE evaluation results show that while there was no high-level evidence based on 86 evaluation indicators, there was 1 study with moderate-level evidence (1%), 44 studies with low-level evidence (51%) and 41 with very low-level evidence (48%) based on other indicators. YSHZT can significantly improve the bone mineral density (BMD) of Ward's triangle, with a mean difference range of 0.03 to 0.12. Different conclusions were reported regarding the BMD of the lumbar spine, femoral trochanter, femoral neck, and hip, as well as bone turnover markers, adverse reactions and other outcome indicators in different SRs and thus still need further study. Conclusions The methodological quality and the evidence quality of the outcome indicators for YSHZT in the treatment of PMOP are poor, and the efficacy and safety of YSHZT in the treatment of PMOP still need to be further verified by more high-quality studies.